(untitled) (Iraqi Journal of Civil Engineering, 2017)
Our cities is desert cities because of desert climate factors in them , this research deals with role of spatial factors in the dust storms of desert cities . Two factors effected in spatial : Difference of elevation and distance from the center city . We found multi relationships between spatial factors and dust storms in Ramadi city , Which these relationship very important in city design and planning such as in objective , urban and rural environment , environmental planning